Validitas dan Reliabelitas Angket Kepemimpinan Transformasional dan Perilaku Kerja Inovatif - Husein Sudrajat; Wawan Samudera (Jurnal Pendidik Indonesia (JPIn), 2021)
The instrument has a crucial function in a study. The accuracy of the data taken is also influenced by the level of validity of the research instrument. The validity of the research instrument will also affect the accuracy of the research conclusions. Therefore, before using an instrument to collect data, its validity and reliability must be tested. This study examines the validity and reliability of the questionnaire instrument variable questionnaire transformational leadership and innovative work behavior. The description of the indicators in the transformational leadership questionnaire include charisma, individual attention, and intellectual stimulation. While the innovative work behavior questionnaire includes seeing opportunities, issuing ideas, fighting for them, and applying them. Analysis of the validity and reliability of this study used the IBM SPSS Statistics 24 program. The results of the validation test of transformational leadership variables and innovative work behavior obtained all items valid, because the Pearson Correlation value was greater than 0.30, then after the data were analyzed with validity, all items that validity was analyzed by reliability test, obtaining the value of Cronbach's Alpha Transformational Leadership Variable 0.765 and Innovative Work Behavior Variable 0.863. So that the value of Cronbach's Alpha if Item Deleted 0.60. Referring to the results of the reliability test, it can be concluded that the transformational leadership bell instruments and innovative work behavior are all valid and reliable